Effects of a combined infection with Paranosema locustae and Beauveria bassiana on Locusta migratoria and its gut microflora. (15th June 2020) - Tan, Shu‐Qian; Yin, Yue; Cao, Kai‐Li; Zhao, Xin‐Xin; Wang, Xiao‐Yu; Zhang, Yu‐Xin; Shi, Wang‐Peng
Abstract: Even though Paranosema locustae is widely used in China as a biological agent for controlling grasshoppers, the mortality rate is initially quite low. This study sought to determine whether the simultaneous use of P. locustae and Beauveria bassiana would be a more effective control strategy. Additionally, changes in the intestinal microbial communities of migratory locusts infected with the two pathogens were analyzed to investigate the roles of gut microbes in pathogen–host interactions. The mortality rate of locusts inoculated with B. bassiana and P. locustae simultaneously was not significantly higher than expected, but the mortality rates of locusts inoculated with B. bassiana 3, 6, and 9 days after inoculation with P. locustae were significantly higher than if their effects were additive, indicating synergism. A MiSeq analysis found that Weissella was the most common bacterium, representing 41.48% and 51.62% of the total bacteria in the mid‐ and hindguts, respectively, and the bacterial declines were greatest during dual infections with B. bassiana and P. locustae . The appropriately timed combined application of P. locustae and B. bassiana was more effective against locusts than either treatment alone. Moreover, the combined inoculation of the two pathogens changed the gut microflora of locusts, indicating the potential relevancy of their synergistic effects on locust control.